Das historische Prosawerk von Bruno Frank - Łukomska-Woroch, Aleksandra (Wydawnictwo Naukowe UAM, 1990)
In many works by B. Frank, one of the most eminent German writers of the 20th century historical problems, critically treated, is dominant. He is often concerned directly with contemporary times. On the example of the main heroes of his historical works the writer conducts a real historical origin of ideas from the past, according to G. Lukács's typology. In his novel “Trenck” (1926) B. Frank shows on the example of the fate of the main hero the realistic picture of Prussia of Frederick William and of the Austrian court during the reign of Maria Theresa. In “Politische Novelle” (1928), devoted to the German statesman, F. Stresemann the writer accounts for the phenomenon of the growing Nazism in Germany. The short story “Der Magier” (1929), devoted to the director Max Reinhard is also a survey of various social and political conflicts of the interwar period. In the novel “Cervantes” (1934) which is a biography of the great Spanish poet and the history of Philip II's rule. Between the historical novel's problems and the problems of Nazi times during which the novel was written there are many analogies. In the novel “Der Reisepaß” (1937) the writer shows the fate of emigrant combined with political situation during the Third Reich. In a little known novel “Die Tochter” (1943) the author presents, against the background of development of the main hero, a critical picture of the reality in Poland, particularly in the Galicia between the two world wars.